EFFORTS TO DEVELOP THE ECONOMY OF BUMDES PRODUCTS ARE VIBRANT IN THE SERIES OF SUMBER RAHAYU VILLAGE THROUGH THE CELEBGRAM ENDORSEMENT SYSTEM AS A SOCIAL MEDIA PROMOTION - Randi Randi; Yulasteriyani Yulasteriyani; Rizki Goffar Ismail; Yosi Arianti (Jurnal Ekonomi, 2022)
Sumber Rahayu Village, Rambang District, Muara Enim Regency. Sumber Rahayu Village in history is a critical forest area and is filled with weeds. In 1981, according to President Soeharto's instructions on transmigration, the land was cultivated and began to be inaugurated by the Governor of South Sumatra in 1982. The main problem that arises in BUMDes Semarak Berseri Sumber Rahayu Village based on an initial survey by researchers is the ineffective marketing of BUMDes products, causing BUMDes to be difficult to develop. So that the focus of this research is how to develop the economy of BUMDes products in the series of Sumber Rahayu Village through the Celebgram Endorsement System as a Social Media Promotion. The results of this study are Efforts to Develop the Economy of BUMDes Products Vibrant in Sumber Rahayu Village Through the Celebgram Endorsement System as Social Media Promotion through Community Participation, Government as a Support System, Marketing Innovation through endorsements, Good planning. The research method used is qualitative research.